Biological Control of Brown Leaf Spot Disease Caused by Curvularia lunata and Field Application Method on Rice Variety IR66 in Cambodia - Huyly Tann; Kasem Soytong (AGRIVITA, Journal of Agricultural Science, 2017)
Curvularia lunata was found to cause a serious rice brown leaf spot in Cambodia. This is the first report of brown leaf spot on rice in Cambodia. All isolates were tested for pathogenicity. Dual culture antagonistic tests showed that Chaetomium cupreum inhibited sporulation of C. lunata when compared to the control. In a pot experiment, C.  cupreum significantly reduced the incidence of brown leaf spot caused by C. lunata. After application of a spore suspension of C. cupreum, Chaetomium-biofungicide and chemical fungicide (tebuconazole) to rice seedlings inoculated with C. lunata, the disease was reduced by 68.79 %, 75.80 % and 72.41 %, respectively. In a field trial, the chemical method gave the best results in all plant parameters, followed by the good agricultural practice (GAP) and organic methods. The chemical method gave the highest panicle/plant, panicle length, panicle weight, grain weight/plant which were different from the GAP and organic methods. The chemical method also gave the best results in filled grain panicle-1, unfilled grain panicle-1, grain weight plot-1, dry hay weight plot-1, biomass weight plot-1 and harvest index, and was significantly better than the GAP and organic methods.